Factors Influencing the Occurrence of Stunting in Toddlers - Amelia Susanti; Mufdlillah Mufdlillah (Green Publisher Indonesia, 2026)
Stunting is a depiction of chronic malnutrition during the growth and development period from the beginning of life. Many factors can cause stunting in toddlers. This literature study aims to identify the factors influencing the occurrence of stunting in toddlers. A literature scoping review was conducted using three databases to search for relevant articles: PubMed, ScienceDirect, and Wiley Online Library. The stages and flow of research article selection followed the PRISMA Flowchart (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). To assess article quality, the researchers used a checklist from the Joanna Briggs Institute. The search yielded 5,571 articles matching the specified keywords; 3,569 duplicates were removed, leaving 2,002 articles selected according to the literature study's objectives. Of these, 46 articles were eligible, and 9 met the review criteria. The review identified several sub-themes on factors affecting the occurrence of stunting in toddlers: a) mother's knowledge; b) maternal education; c) economic status; d) history of birth weight (BBL); e) maternal body mass index (BMI); f) breastfeeding history. Insufficient energy and protein intake, lack of maternal knowledge, low maternal education, low family income, and maternal BMI status are relevant factors for stunting in toddlers. Efforts to prevent stunting in toddlers can include communication, information, and education; health promotion or counseling; and workshops.